Gambaran Tingkat Pengetahuan, Sikap Dan Perilaku Higiene Sanitasi Pada Penjamah Makanan Di Instalasi Gizi RSUD Pemangkat - Elisa, Dela; Saepudin, Malik; Martini, Martini (Jurnal Riset Kesehatan Masyarakat, 2024)
Food sanitation hygiene is an implementation of healthy and safe food by increasing the degree of health that must pay attention to the level of food quality bacteriologically, chemically, and physically. Food handlers at the Nutrition Installation of Pemangkat Hospital do not use gloves when processing food. The purpose of this study to describe the level of knowledge, attitudes, and behavior of sanitation hygiene on food handlers at the Nutrition Installation of Pemangkat Hospital. This research is descriptive, it describes the level of knowledge, attitude, and hygiene behavior of food handlers at the Nutrition Installation of Pemangkat Hospital. The results of the field analysis of the description of the level of knowledge, attitudes, and hygiene behavior of food handlers at the Nutrition Installation of Pemangkat Hospital which can be explained that the level of knowledge of food handlers is 100% the good category, the attitude of food handlers is 90%  the good category, and the behavior of food handlers by 100% with good category. The conclusion in this study is that 10% of food handlers have sufficient attitudes, this is due to the bad attitude of the handlers so that it can affect the level of sanitation hygiene in food.